Preoperative serum 25-hydroxycalciferol levels in Kherson-region patients with cataract only, cataract plus glaucoma or cataract plus high myopia (Ukrainian Journal of Ophthalmology, 2025)
Background: The contribution of cataract to the total prevalence of eye disease in Ukraine increased from 14.7% in 2001 to 15.9% in 2011. Studies have shown that 15% to 76% of eyes with glaucoma have cataract. In addition, cataract associated with myopia is 45-fold more frequent than cataract associated with other refractive errors. Blood 25-hydroxycalciferol is a biologically active substance that reflects vitamin D levels in man. Vitamin D is a general term used to denote vitamin D2 (also called ergocalciferol) and vitamin D3 (also called cholecalciferol). 25-hydroxycalciferol plays a key role in the preservation of the structure of the connective tissue, regulation of inflammatory processes, and energy exchange in the body, but its role in patients with cataract only, cataract plus glaucoma or cataract plus high myopia, however, has been poorly studied.Purpose: To assess preoperative serum 25-hydroxycalciferol levels in Kherson-region patients with cataract only, cataract plus primary open-angle glaucoma (POAG) or cataract plus high myopia.Material and Methods: Immediately before they underwent cataract surgery during November 2017 to April 2018, 128 Kherson-region patients underwent assessment of their serum 25-hydroxycalciferol levels. Patients were divided into three disease groups depending on the presence of POAG or high myopia: group 1 (controls; cataract only; n = 38), group 2 (cataract plus POAG; n = 36) and group 3 (cataract plus high myopia; n = 54). Age groups and men and women within disease groups were assessed separately for serum 25-hydroxycalciferol levels. Serum samples were analyzed for 25-hydroxycalciferol using enzyme immunoassay (IDS, Germany).Results: Patients of all disease groups showed substantial deficiency in serum 25-hydroxycalciferol levels compared to a norm of 30 ng/ml or more. In each disease group, women showed lower serum 25-hydroxycalciferol levels than men, and the difference was significant for groups with cataract plus myopia (Р = 0.04) and cataract plus glaucoma (Р = 0.006), but not for the cataract-only group.Conclusion: We found low serum 25-hydroxycalciferol levels in all patients with age-related cataract, especially in those with concomitant high myopia or POAG. The study patients older than 75 years showed severely deficient serum 25-hydroxycalciferol levels, with no significant difference among study groups.
Keywords: cataract; high myopia; 25-hydroxycalciferol